Elevated Osteopontin and Interferon Gamma Serum Levels and Increased Neutrophil-to-Lymphocyte Ratio Are Associated With the Severity of Symptoms in Schizophrenia - Kovács, Márton Áron; Tényi, Tamás; Kugyelka, Réka; Prenek, Lilla; Hau, Lídia; Magyar, Éva Erzsébet; Herold, Róbert; Balogh, Péter; Simon, Diána (Frontiers in Psychiatry, 2020)
Inflammation and immune dysregulation could contribute to the pathogenesis of schizophrenia. Osteopontin (OPN) is a cytokine-like glycoprotein involved in inflammation and in modulating immune responses, and it can also directly modify the cytokine expression and survival of microglia. Furthermore, elevated gene expression of OPN in first episode psychosis has recently been described, but to date OPN level has not been investigated in schizophrenia. Imbalance of T-helper subtypes could also represent a vulnerability factor for schizophrenia. In this study, we analyzed the concentration of OPN, levels of cytokines associated with T-helper subtypes: IFNy for Th1, IL-10 for Th2, IL-8 for Th17, and neutrophil-to-lymphocyte ratio (NLR) in 22 patients with schizophrenia assessed for the intensity of their symptoms by PANSS and CGI scores. Serum OPN, IFNy, IL-10, and IL-8 concentrations were measured by ELISA kits and NLR was calculated from blood count. We found significant correlation between the level of OPN and PANSS-total and PANSS-general scores. IFNy level and NLR showed significant correlation with PANSS-total, PANSS-positive, PANSS-general and CGI score. Among the measured markers antipsychotic therapy only had significant effects on NLR and OPN level, both of which were significantly reduced after long-term antipsychotic treatment. Our results indicate that elevated OPN and IFNy concentrations, and increased NLR are associated with severe symptoms in schizophrenia and suggest the importance of Th1 subtype in patients with high PANSS-positive and PANSS-general subscore. Significant correlation between NLR and PANSS scores strengthens the inflammation hypothesis of schizophrenia.